INVESTIGATION OF ANALGESIC, ANTIOXIDANT, AND CYTOTOXIC PROPERTIES OF THE ETHANOLIC EXTRACT OF STREBLUS ASPER (ROOTS) - DAS, ANANTA KUMAR; PARUL, ROZINA; ISLAM, MD. MONIRUL; GHOSH, APU CHANDRA; ALAM, MD. JAHIR (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This study evaluated the analgesic, antioxidant, and cytotoxic effects of ethanolic extract of Streblus asper roots. Methods: Analgesic activities were carried out using paw licking and writhing tests. The extract was used at doses of 250 and 500 mg/kg per orally in Swiss albino mice of body weight 25–30 g. Antioxidant properties were investigated using 1, 1-diphenyl-1-picrylhydrazyl free-radical scavenging assay, total phenol content, total flavonoid content as well as reducing power capacity. The cytotoxic activity was determined by the Brine Shrimp lethality bioassay. Results: The ethanolic extract of S. asper roots showed a significant effect in the formalin test (p<0.01). They also exhibit the highest analgesia (p<0.01) in the acetic acid-induced writhing model as well. The extract possessed antioxidant effects in all the models. It possessed a good cytotoxic activity. Conclusion: The results suggested that S. asper root extract has a suitable analgesic, antioxidant effect as well as significant cytotoxic potential.